The Effect Of Current Ratio, Debt To Assets Ratio, Total Assets Turnover, And Company Size On Company Value (Tobin's Q) In Coal Sub Sector Companies Listed On The Indonesia Stock Exchange Period 2018-2022 - Alfitaria Alfath Nuur; Esi Fitriani Komara (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of the current ratio, debt to assets ratio, total assets turnover, and company size on firm value (Tobin’s Q) in coal sub sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. This study utilizes information from financial reports listed on the IDX, with a quantitative approach. The type of data used is secondary data with a population of 31 coal sub sector companies and samples were acquired from upwards of 16 companies utilizing the purposive sampling method. The data analysis technique was done utilizing panel data regression. The results of this study show that current ratio and company size have a positive effect on firm value (Tobin’s Q), while debt to assets ratio and total assets turnover have an effect on firm value (Tobin’s Q).